2014
DOI: 10.1007/s00436-013-3742-3
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of Fendona 6SC® treated bednets and Interceptor® long-lasting nets against Anopheles gambiae s.l. in Burkina Faso

Abstract: Insecticide-treated bednets play a cornerstone role in the efforts to control malaria. Bednets entomological efficacy is the determinant factor of their use to control malaria. In this study, we compared under laboratory conditions, the efficacy of two long-lasting nets (PermaNet versus Interceptor) and two treatments kits K-O TAB (deltamethrin) versus Fendona 6SC (alpha-cypermethrin) against Anopheles gambiae s.l. malaria vectors. The efficacy of washed and unwashed bednets was assessed by contact bioassays u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…fluviatilis was greatly deterred from entering the huts and those mosquitoes that entered the huts were prevented from feeding on the host, despite the presence of holes on the nets, indicating a signiÞcant and comparable personal protection offered by the LNs and SPs. Different results were obtained for vectorsÕ exiting in response to the SPs and LNs when used in experimental huts; some reported induced exophily (Badolo et al 2012, Malima et al 2013) and others observed insigniÞcant difference relative to the control (Mosha et al 2008). Such difference depends also on the innate characteristic of the targeted vector species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fluviatilis was greatly deterred from entering the huts and those mosquitoes that entered the huts were prevented from feeding on the host, despite the presence of holes on the nets, indicating a signiÞcant and comparable personal protection offered by the LNs and SPs. Different results were obtained for vectorsÕ exiting in response to the SPs and LNs when used in experimental huts; some reported induced exophily (Badolo et al 2012, Malima et al 2013) and others observed insigniÞcant difference relative to the control (Mosha et al 2008). Such difference depends also on the innate characteristic of the targeted vector species.…”
Section: Discussionmentioning
confidence: 99%
“…However, Corbel et al (2004) observed a higher deterrence (83Ð 89%) against Anopheles gambiae with nets treated with 50, 100, 250, and 500 mg permethrin/ m 2 . But, against the same vector species, there was no clear evidence of deterred effect of alphacypermethrin-treated (Interceptor) and deltamethrin-treated (PermaNet) LNs (Malima et al 2013, Badolo et al 2012. In an experimental hut trial of bed-nets impregnated with SPs or organophosphate (OP) insecticide for mosquito control in The Gambia, it was concluded that permethrin tends mainly to deter mosquitoes from house entry, enhancing personal protection, whereas the OP insecticide kills higher proportions of the endophilic mosquitoes, which would give better community protection against malaria transmission (Miller et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the proportion of each entomological outcomes and the level of significance between the treatments and between the control for each entomological outcomes, the XLSTAT software (Addinsoft, Berkeley, CA, USA) was used, as done previously [29,30]. The numbers of mosquitoes collected in the huts with different treatments were analysed by negative binomial regression.…”
Section: Experimental Hut Trialmentioning
confidence: 99%
“…Experimental hut trial: To calculate the proportion of each entomological outcomes and the level of significance between the treatments and between the control for each entomological outcomes, the XLSTAT software was used, as before. The confidence limits of these parameters were calculated and the proportions were compared using a chi-square test with a significance limit of 0.05 [31,43,50,51].…”
Section: Discussionmentioning
confidence: 99%